Yessotoxin activates cell death pathways independent of Protein Kinase C in K-562 human leukemic cell line. Issue 7 (October 2015) - Fernández-Araujo, Andrea; Alfonso, Amparo; Vieytes, Mercedes R.; Botana, Luis M.
Highlights YTX treatment modifies cPKC and PKCδ levels in nuclear and cytosolic localizations. YTX effect over PKC isozymes is PDE4A dependent. Cellular death activated by YTX is cPKC and PKCδ-independent but PDE4A-dependent.